Juvéderm® Volbella™ in the perioral area: a 12-month prospective, multicenter, open-label study - Eccleston D; Murphy DK (Dove Medical Press, 2012)
David Eccleston,1 Diane K Murphy21Private Practice, Birmingham, UK; 2Allergan, Santa Barbara, CA, USABackground: Hyaluronic acid dermal fillers are frequently used for lip augmentation, and a new filler has been developed with characteristics especially suited for the lips.Methods: Four European sites treated 60 subjects with Juvéderm® Volbella™ injectable gel in the perioral area, and subjects returned to the clinic at 1, 3, 6, 9, and 12 months for follow-up. The primary effectiveness endpoint established a priori was a Month 3 responder rate on the 4-point Lip Fullness Scale (LFS) of ≥40% and statistically > 0%, where responders improved ≥ 1 point from baseline on the investigator's assessment of LFS. At follow-up, subjects assessed lip fullness goal achievement, the look and feel of their lips, and their satisfaction with the effects of treatment.Results: The Month 3 LFS responder rate was 93.2% (P < 0.0001), so the primary endpoint was met, and clinical effectiveness was demonstrated. The responder rate over time showed that 78.0% of subjects still had improved lip fullness at Month 9 and 48.3% at Month 12. After treatment 98.3% of subjects reported that their lip fullness goal had been achieved, and this was maintained at 86.4% at Month 9 and 56.9% at Month 12. At Month 1, 81.0% of subjects reported that their lips felt smooth, and 91.4% reported that their lips looked natural (scores of 7–10 on an 11-point scale, where 0 was an unfavorable outcome and 10 was a favorable outcome). Similarly, 96.6% of subjects reported being satisfied (scores between 7 and 10 on an 11-point scale where 0 = very dissatisfied, 10 = very satisfied) at Month 1, and by Month 12 more than 80% of subjects were still satisfied. There were no severe adverse events related to treatment.Conclusion: Juvéderm® Volbella™ injectable gel is well tolerated and has been demonstrated to provide a smooth and natural improvement in lip fullness that lasts for up to 1 year.Keywords: dermal filler, hyaluronic acid, lips, patient satisfaction